2013
DOI: 10.7150/ijbs.6978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Alternative Splicing of a Sodium Channel and DSC1 Ortholog Genes in Liposcelis bostrychophila Badonnel (Psocoptera: Liposcelididae)

Abstract: Alternative splicing greatly contributes to the structural and functional diversity of voltage-gated sodium channels (VGSCs) by generating various isoforms with unique functional and pharmacological properties. Here, we identified a new optional exon 23 located in the linker between domains II and III, and four mutually exclusive exons (exons 27A, 27B, 27C, and 27D) in domains IIIS3 and IIIS4 of the sodium channel of Liposcelis bostrychophila (termed as LbVGSC). This suggested that more alternative splicing ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Exclusion of both alt 3‐v1 and v2 results in the third variance v3 , and could also generate a non‐functional channel owing to the absence of IIIS3–S4, which is consistent with the absence of exon 3 in VmNa . In sodium channels of insects, the variances in this splice site that would generate truncated proteins are detected in several spices, such as G3 in BgNa v and 27C in LbVGSC . Although the splicing mechanisms are different, the incomplete protein structure in IIIS4 will cause a loss of partial function.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Exclusion of both alt 3‐v1 and v2 results in the third variance v3 , and could also generate a non‐functional channel owing to the absence of IIIS3–S4, which is consistent with the absence of exon 3 in VmNa . In sodium channels of insects, the variances in this splice site that would generate truncated proteins are detected in several spices, such as G3 in BgNa v and 27C in LbVGSC . Although the splicing mechanisms are different, the incomplete protein structure in IIIS4 will cause a loss of partial function.…”
Section: Discussionmentioning
confidence: 78%
“…20 In sodium channels of insects, the variances in this splice site that would generate truncated proteins are detected in several spices, such as G3 in BgNa v and 27C in LbVGSC. 19,52 Although the splicing mechanisms are different, the incomplete protein structure in IIIS4 will cause a loss of partial function. It was reported that alternative splicing of mutually exclusive exons G1 to G3 generates three splicing variances with different sensitivities to deltamethrin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation